Exploration of STEM Reforms for Developing an Effective Large‐scale, Research‐based Policy in the UAE STEM - AL QURAAN, ELAINE (2017)
Background: Mathematics, science, engineering, and technology are subjects believed to reflect people’s cultural achievements that power the economy and development, and at the same time constitute essential aspects of the lives. Educators admit that it is vitally important that integrated STEM education in K-12 schools aligns with 21st century skills, creates new jobs, increases competition in the global economy, and educates the next generation of STEM professional. The implementation of STEM is at its early stage in UAE and calls for an integrated framework for effective implementation in K-12 education. Purpose: The purpose of this study was to develop a policy and implementation framework in the UAE by identifying critical elements of an integrated STEM education and key factors related to the implementation of an integrated STEM curriculum in K-12 schools in UAE. Methods: The researcher employed Exploratory Sequential Mixed Methods for this study. The mixed research methods included both qualitative and quantitative methods. These include document analysis, teacher questionnaire survey, teacher and coordinators’ interview surveys, school and district leaders’ interview survey, and classroom observations. Results: The findings of this study proposed the policy recommendation framework for integrated STEM implementation in UAE schools. It can be concluded from the findings that STEM implementation can be categorized into structural and interpersonal implementation dimensions. In addition, Assessment, Connection, Curriculum and Delivery, Leadership, Pedagogical Content Knowledge, Technology and Resources are important factors associated with STEM integration and implementation in UAE schools. The findings also suggested that curriculum, pedagogy, leadership, professional development, and assessment are important elements associated with STEM integration and implementation in UAE schools. The study proposed policy recommendation based on policy planning, leadership, establishing STEM, professional development of teachers, communities and businesses’ role, technology and resources, curriculum design and assessments, pedagogy and learning, capacity building and motivation, awareness and promotion, society’s adaptations, and exposure and employment. Implications/Contributions: It was evident that teachers and school leaders are facing many challenges as they struggled to figure out the best ways to plan and implement STEM in UAE. The isolation that they faced as pioneers in implementing these kinds of courses in K-12 education was also evident. Examining of an integrated policy recommendation for STEM framework could help all educational leaders to understand this phenomenon better.